PENGARUH KOMITMEN ORGANISASI, ETIKA KERJA DAN KOMUNIKASI TERHADAP LOYALITAS PEGAWAI BPJS KESEHATAN CABANG KOTA BENGKULU - Syofian, Syofian; Waliamin, Janusi (Universitas Prof. Dr. Hazairin SH, 2022)
The purpose of this research was to determine and analyze the effect of organizational commitment, work ethics and communication on employee loyalty. This research is an explanatory research with a quantitative approach. Total population of 50 people, sample in this study amounted to 50 people, all employees of the Bengkulu City Branch of BPJS or by using the probability sampling. Data analysis techniques in this study are instrument test, classical assumption test, multiple linear regression analysis. The results of this study explain that organizational commitment has a positive and significant effect on employee loyalty, work ethics has a negative and no significant effect on employee loyalty, and organizational communication has a positive and significant effect on employee loyalty. The contribution of this research is for the Bengkulu City Branch of the BPJS to be taken into consideration, input and suggestions for increasing work loyalty towards employees of the Bengkulu City branch of the Health BPJS office regarding organizational commitment, communication work ethics and employee loyalty